DHDMIQK(KAP): a novel nano-delivery system of dihydroxyl-tetrahydro-isoquinoline-3-carboxylic acid and KPAK towards the thrombus. Issue 36 (26th August 2016) - Feng, Qiqi; Zhao, Ming; Gan, Taiping; Zhu, Haimei; Wang, Yaonan; Zhao, Shurui; Wang, Yuji; Wu, Jianhui; Peng, Shiqi
Abstract : N -[( S )-6, 7-Dihydroxy-1, 1-dimethyl-1, 2, 3, 4-tetra-hydroisoquinoline-3-carbonyl]-Lys(Pro-Ala-Lys) was presented as a novel nano-delivery of ( S )-6, 7-dihydroxy-1, 1-dimethyl-1, 2, 3, 4-tetra-hydroisoquinoline-3-carboxylic acid and Lys-Pro-Ala-Lys towards the thrombus for the first time. Abstract : Vascular thrombosis is a major risk of the onset of stroke and so novel therapeutic candidates have been attracting interest. In this context, here docking based computer assisted screening and mesoscale simulation were used to design N -[( S )-6, 7-dihydroxy-1, 1-dimethyl-1, 2, 3, 4-tetrahydroisoquinoline-3-carbonyl]-Lys(Pro-Ala-Lys), DHDMIQK(KAP), for inhibiting P-selectin expression. In vitro, 1 nM of DHDMIQK(KAP) effectively down-regulated P-selectin expression. In water, in rat plasma and in the solid state DHDMIQK(KAP) formed nanoparticles of a size capable of suitable delivery in the blood circulation. FT-MS and NOESY 2D NMR spectra showed DHDMIQK(KAP) formed hexamers, identified the intermolecular interactions of the hexamer, and assigned the hexamer a butterfly like conformation. Transmission electron microscopy, scanning electron microscopy and atomic force microscopy (AFM) imaged DHDMIQK(KAP) forming size-suitable nanoparticles for safe delivery in the blood circulation. In particular, AFM images showed that the nanoparticles effectively adhered onto the surfaces of the platelets. In vivo DHDMIQK(KAP) lysed the thrombus and inhibited thrombosis with a minimal effective dose of 0.01 nmol kg −1 . FT-MS spectrum analyses defined a specific distribution of DHDMIQK(KAP) in the thrombus, but not in the blood and vital organs. Therefore, DHDMIQK(KAP) should be a novel nano-delivery system of 6, 7-dihydroxyl-1, 2, 3, 4-tetrahydroisoquinoline-3-carboxylic acid and KPAK to target the thrombus.